2019
DOI: 10.1080/26395916.2019.1687585
|View full text |Cite
|
Sign up to set email alerts
|

Values held by Swedish primary school students towards forest ecosystems and the relevance for a nature’s contributions to people approach

Abstract: How the concept of value is defined within ecosystem services operates as a filter through which important ecosystem features are identified by the specific benefits they provide to society and individuals. This value narrative reflects intrinsic and instrumental concepts which have been challenged by the Nature's Contributions to People approach in additionally highlighting the importance of relational values, stemming from socio-cultural and ethical dimensions of human relationships with nature and ecosystem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 69 publications
(89 reference statements)
0
4
0
Order By: Relevance
“…The latter is valued as a metaphor for disturbed agroecological relationships. Moreover, the content analysis method applied in this study reveals a more personal sense of relational values (Chan et al, 2018;Goodwin et al, 2019) underpinning non-material NCP, such as sacredness and devotion to land, social cohesion, emotional attachment, reciprocity, cultural identity and symbolic associations.…”
Section: Conceptual Approachmentioning
confidence: 96%
“…The latter is valued as a metaphor for disturbed agroecological relationships. Moreover, the content analysis method applied in this study reveals a more personal sense of relational values (Chan et al, 2018;Goodwin et al, 2019) underpinning non-material NCP, such as sacredness and devotion to land, social cohesion, emotional attachment, reciprocity, cultural identity and symbolic associations.…”
Section: Conceptual Approachmentioning
confidence: 96%
“…Nonetheless, we are encouraged to see ecosystem services increasingly emerge in the literature of environmental education and environmental education appearing in the literature of ES-NCP. For example, recent studies include the study of Hutcheson et al (2018) on the environmental education as a cultural ecosystem service, the study of Barracosa et al (2019) on the use of ocean literacy to mainstream the ES concept in both formal and informal education settings, the study of Goodwin et al (2019) on the exploration of values held by primary school students, and the study of Almers et al (2020) on the functional meaning that preschool-aged children assign to different material aspects of their schoolyards. We are hopeful that this important research direction will continue.…”
Section: Embodied Childhood Nature Experiencementioning
confidence: 99%
“…When dealing with complex socio-ecological interlinkages that touch on numerous aspects of human ways of life and ecological processes, effective implementation of findings means that multiple areas of policy should be addressed simultaneously. As the results of Goodwin et al (2019) suggest, information on the relationships that young people of diverse backgrounds develop with nature is important to multiple areas of policy, from education, to health, and even migration. Just as the science underpinning these findings benefits from taking an interdisciplinary approach, the cross-cutting nature of the policy spheres with which they interact must also be taken into account, so that results are usable and able to be communicated effectively.…”
Section: Work At the Science-policy Interface Is Cross-cutting In Natmentioning
confidence: 99%
“…Much could be achieved through transforming current education (Goodwin et al 2019) and curricula related to sustainability (in natural as well as social and human sciences). As some of the results of Goodwin et al (2019) showed, of those students whose relationships with nature were the most challenged were also among the most curious to learn more. This suggests that education has a powerful role to play in developing relationships that future generations develop towards nature.…”
Section: Education Opens the Door To Stronger Science-policy Interfacmentioning
confidence: 99%